PENGEMBANGAN MATERI KOMPETENSI DASAR SEJARAH BERDASARKAN TEORI DIFFUSI BUDAYA: ANALISIS ANASIR BUDAYA JAWA DAN SULAWESI SELATAN DI KERAJAAN SUMBAWA - Ismain, Kasimanuddin (Jurnal Sejarah dan Budaya, 2010)
Abstract: The specified formulation of History Basic Competence in school curriculum contains competence, concept and material space that has to be developed. Using interdisciplinary approach, Diffusion theory from Anthropology is useful for developing basic competence material of traditional state life. Enlarging of Majapahit and Gowa power area has been diffused cultural traits from Java and South Sulawesi into political building and Sumbawa Kingdom culture. The model of concentric area structure has been diffused from Kingdom of Majapahit (then Mataram) and has been adopted into city structure and area of Sumbawa Kingdom. The government system based on Hadt Syaraâ and model of palace model has been diffused from Kingdom of Gowa to Kingdom of Sumbawa. Theory of cultural diffusion enrich material perspective about relations among traditional states.